A study of the effects of Related Parties Transactions on the Agency costs - Mohammad Banafi; Ali Ghayouri Moghadam; Mohammad Mehdi Dana (مطالعات تجربی حسابداری مالی, 2015)
The aim of this research is to find out whether Related Parties Transactions can produce a meaningful influence on the agency cost or not. To answer this question two definitions of agency cost are employed: Tobin’s Q Ratio and mutual relationship between the chance of development and free cash flow. Having these two definitions in mind we studied the effects of transactions with Related Parties on the agency cost. We studied 55 companies involved in Tehran Stock market Exchange (TSE)The results show that when we measure the agency cost using Tobin’s Q Ratio, the effect of the transactions with Related Parties on the agency costs is positive and meaningful but when the second measurement that is, the relationship between the chance for development and the free cash flow, is applied the influence is not meaningful. The findings show that Related Parties Transactions is in accordance with conflict of interest theory, this means that transactions can reinforce the opportunistic behavior of the managers, result in the destruction of the interest and disadvantage the owners.